CALCULATION OF RUNOFF DISCHARGE ON CV. CLASIGI OF SORONG DISTRICT, WEST PAPUA PROVINCE: PERHITUNGAN DEBIT LIMPASAN PADA CV. KLASIGI KABUPATEN SORONG PROVINSI PAPUA BARAT - Wilson Woodrow Gerenop Ameto (INTAN Jurnal Penelitian Tambang, 2024)
Klasigi is a sirtu mining company located in Klasigi Village, Makbon District, Sorong Regency, West Papua Province. CV. Klasigi conducts mining using an open pit mining system with the quarry method. The mining system method used usually forms a depression, so that when it rains it has the potential to cause flooding in the mining area and mining roads. Based on the results of observations made by researchers in the field, the area that is the problem is the area around the mining road location. This is caused by rainfall that falls and forms uncontrolled surface runoff, so efforts are needed to overcome this problem. The aim to be achieved in this research is to find out how large the cathment area value is and how large the surface runoff discharge value is at this research location. Based on the results of the analysis of Sorong city rainfall data for the last 10 years, it was found that the standard deviation was 0.0683, the variance coefficient was 0.0506, the skewness coefficient was -0.1645, and the planned rainfall was 13.59 mm/day, the rain intensity was 4, 7114 mm/hour, the cathment area value is 0.062 km2, and the runoff discharge is 0.073 m3/s.